Phenylethyl isothiocyanate induces oxidative damage of porcine kidney cells mediated by reactive oxygen species. Issue 2 (20th December 2019) - Zhu, Yuanyuan; Liu, Shuiping; Yan, Sisi; Wang, Ji; Zhang, Linyu; LI, Xin; Wen, Lixin; Wu, Jing
Abstract: The aim of this study is to confirm the toxic effect of phenylethyl isothiocyanate (PEITC) on porcine kidney cells (PK‐15) and explore the effect of oxidative damage mediated by reactive oxygen species (ROS) induced by PEITC in PK‐15 cells. Porcine kidney cell line (PK‐15) was treated with PEITC (2, 5, and 10  µM) for 24 hours, and the oxidative damage mediated by PEITC through ROS was investigated. The survival rate of PK‐15 cells decreased in a dose‐dependent manner after the treatment of PEITC in a dose‐dependent manner. A high concentration of PEITC (10 µM) can change cell morphology, increase the content of malondialdehyde, ROS, and lactate dehydrogenase, and decrease the activity of SOD, CAT, GSH‐PX, and GSH. PEITC has a toxic effect on PK‐15 cells by inducing oxidative stress in PK‐15 cells through the generation of ROS.